Effect of insertion/deletion polymorphism of angiotensin-converting enzyme gene on efficacy of antihypertensive therapy with angiotensin II receptor blockers - E. V. Rebrova; E. V. Shikh (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2024)
The efficacy of the antihypertensive therapy may be related to genetic factors that can influence not only the degree of the blood pressure (BP) elevation but also contribute to the interindividual variability of response to the antihypertensive treatment.The aim of the work was to study pharmacodynamic parameters of the therapy efficacy with angiotensin II receptor blockers in the form of monotherapy and as part of combined drugs in patients with the arterial hypertension depending on the genetic features of patients - polymorphism of the gene encoding angiotensin-converting enzyme, or I/D-polymorphism.Materials and methods. The study included 179 patients of the Moscow region with a first-diagnosed arterial hypertension (AH) of 1-2 degree, including 141 (78.8%) women and 38 (21.2%) men aged from 32 to 69 years. By a simple randomization method, the patients were randomly allocated into groups receiving irbesartan and valsartan as mono- or combination therapy with hydrochlorthiazide. After 3 weeks of this pharmacotherapy, the presence of rs4646994 Alu Ins / Del genetic polymorphism of the angiotensin-converting enzyme (ACE) gene and the minimum equilibrium concentration of angiotensin II receptor blockers (ARBs) were determined.Results. The patients treated with irbesartan, the D/D genotype carriers, were significantly less likely to reach the target BP and more likely to require a pharmacotherapy intensification compared to I/D heterozygotes (p=0.042 and p=0.058, respectively) and I/I homozygotes (p=0.011 and p=0.011, respectively). The patients treated with valsartan, the D/D genotype carriers, significantly more often reached the target BP and significantly less often required a pharmacotherapy intensification than the I/D genotype carriers (p=0.05 and p=0.05, respectively). Herewith, at the end of the study, according to the results of the office BP measurements and daily BP monitoring, the target BP achievement was not significantly correlated with the I/D polymorphism of the ACE gene.Conclusion. When personalizing the AH therapy in patients of the Moscow region, the genotype I/I carriers by I/D polymorphism of the ACE gene, can be recommended irbesartan in the form of mono- or bicomponent therapy as a starting therapy of ARBs; the D/D genotype carriers can be recommended valsartan. A more pronounced decrease in the daytime systolic BP (SBP), the daytime diastolic BP (DBP) and the nighttime SBP variabilities in the valsartan group of patients, the D allele carriers may indicate a more persistent effect of the antihypertensive therapy.